SNP analyzer – A tool to analyze large sets of genetic markers accounting for linkage. (December 2017) - Kling, D.
Abstract: This study presents the development of new software to analyze large sets of genetic markers. In the era of next generation sequencing and high density SNP arrays there is a need for new computer tools to adequately analyze the output. In addition to performing pair-wise relationship computations our software can be used to conduct simulations to obtain expected values for the likelihood ratios (LR). Simulations will give a general idea to when a case can be solved prior to actually sending samples for analyzes. The software, implementing an easy interface, will be most useful for labs obtaining data from clients (or directly using) services provided by companies such as 23andMe or FamilyTreeDNA . In addition, it can use population frequency data from the 1000 Genomes project covering several continents.